EFFECT OF GRADUAL HIGH SALINITY ON SOME STRESS PARAMETERS (GLUCOSE,TOTAL PROTEIN AND LACTATE) IN BLOOD PLASMA OF COMMON CARP - & Al- Hilalli, Al- Khshali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The present study was conducted to investigate the effect of high salinity on the some stress parameters of common carp (Cyprinus carpio) which gradually exposed to salt concentrations of 5, 10 and 15g/liter, as well as tap water (control 0.1g/liter) for 90 days .80 fish were randomly distributed on eight glass tanks with 2 replicates as 10 fish / replicate at average weight of 15 ± 3 g to study the effect of salinity on the Total protein , Glucose ,and Lactate in blood plasma , Fish were fed during the trial on commercial diet with 31.9 % protein content.. Results showed that an increase in the total protein to 4.98 and then decrease to 4.60  and 3.90 g/100 cm3 when the salinity increased to 5, 10 and 15 g/l respectively, compared with the control treatment (4.94 g/100 cm3).  Glucose reached 75.11, 91.20 and 95.17 mg/100 ml at the concentrations of 5, 10 and 15 g/l respectively, compared with the control treatment (66.64 mg/100ml). Lactate also increased to 43.12, 45.38  and 48.53  mg/100 ml , when the salinity increased to  5 , 10 and 15 g/l respectively, in comparison with control treatment  (40.65 mg/100 ml) .